Manjusri in Nepali Context: A Case of Chobhar (The Batuk, 2026)
This study explores the historical and religious background of the Kathmandu valley with mythological association of Manjusri, who is regarded as creator of the valley. It elucidates the origins of Manjusri and his significance across Buddhist traditions Mahayana, Vajrayana and Theravada along with key sutras. Employing descriptive qualitative method - literature review as a secondary source, key informant interviews, consultation with local residents and direct observation at Chobhar, the site associated with the legendary draining of the lake (Nagarhada or Kalidaha) - it investigates different perspectives on inner Buddhism, Sakyamuni Buddha, Saraswati (in Hindu myth) and Manjusri that appear as myth within Buddhist and Hindu worldviews. Despite being regarded as a distinguished and honorable figure often assumed to be a god of wisdom, creator and power in various places exact identity of Manjusri remains a subject of dilemma. This study contributes to understand the interplay of myth, history and religious identity of Manjusri in Nepali cultural landscape.